2007
DOI: 10.1080/00016480601075357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electronystagmography results with dynamic posturography findings in patients with vestibular schwannoma

Abstract: C5S and C6S of VS patients with normal caloric and rotational studies were significantly higher than in VS patients with either asymmetry on both rotational and caloric test results (p<0.001 for both C5S and C6S) or normal rotational studies and asymmetry on caloric testing (p<0.001 for both C5S and C6S). Neither C5S nor C6S were significantly different between patients with asymmetry on caloric testing and normal rotational studies and patients with asymmetry on both rotational and caloric testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Gouveris et al found that VS patients with asymmetry on caloric testing had lower scores for condition 5 and 6 compared with subjects with normal caloric response [18]. These results suggest that SVN involvement accompanies low scores for condition 5 and 6 in posturography testing.…”
Section: Discussionmentioning
confidence: 81%
“…Gouveris et al found that VS patients with asymmetry on caloric testing had lower scores for condition 5 and 6 compared with subjects with normal caloric response [18]. These results suggest that SVN involvement accompanies low scores for condition 5 and 6 in posturography testing.…”
Section: Discussionmentioning
confidence: 81%
“…The central compensation achieved preoperatively is of crucial importance for the faster and more successful rehabilitation of the patient postoperatively. The neuro-otology laboratory, especially by means of electronystagmography [27] and dynamic posturography [28], can help physicians evaluate vestibular function and balance in these patients preoperatively.…”
Section: Disequilibrium and Unsteadinessmentioning
confidence: 99%
“…For example, caloric tests are frequently abnormal, even if origin of VS is commonly the inferior vestibular nerve (IVN). The preoperative caloric tests, even if frequently performed (1,3), have never been studied in a large series of patients, with regard to intraoperative and postoperative results. Therefore, the aim of this study was to focus on caloric tests in a large series of patients with VS, according to the following: 1) age of the patients and preoperative clinical symptoms duration, 2) preoperative parameters (pure-tone average [PTA], speech audiometry, ABR, tumor size, and surgical approach), 3) intraoperative tumor adherence between the tumor capsule and the nerves, and 4) postoperative results (facial function and hearing preservation).…”
mentioning
confidence: 98%